Russians about Development Assistance : Findings of Public Opinion Research - In-Depth Interviews with Opinion Leaders - Leveda Center; Markov, Andrei; Felzer, Sharon; Markova, Svetlana (World Bank, Washington, DC, 2017)
U.K. Department for International Development (DfID)